Multilayered Hybrid Nanofibers as Extreme Ultraviolet Target Irradiated with Low Energy Nd:YAG Laser - Ge1, Liqin; Ji1, Jianyu (Asian Journal of Chemistry, 2011)
The extreme ultraviolet (EUV) light source with a wavelength of 13.5 nm has been believed to be the next generation of light source, which can be produced by laser produced plasmas. By now, Xe, Li, or Sn contained compounds have been used as the target materials, among which Sn target has attracted great attentions for its relative high conversion efficiency, for relatively lower laser intensity of ca. 1010 W/cm2. In this paper, we reported a new type of Sn contained nanofibers as extreme ultraviolet target induced with low energy Nd:YAG laser. The nanofibers were fabricated through the combination of the layer-by-layer technique with the electrospinning method. SEM image shows that the obtained multilayer hollow fibers were collapsed because of the solvent evaporation which was consistent with previous results.